URGENSI HUKUM EKONOMI ISLAM DALAM PEMBANGUNAN EKONOMI NASIONAL DI ERA PASAR BEBAS - Mushafi, Mushafi (Universitas Nurul Jadid, 2015)
The Islamic law has an important role in the national law system. It becomes breaths and spirits the formulation of national law, then there are also other laws. It is as a manifestation ideals of legal establishment which is not only formed the norms or regulations formally but also expected to be the spirit moral formation of the nation,and equitable social order. Ironically, a little awareness from Government’s implementation of Islamic law in practice the national economic development even though the spirit of Islamic economics is not being opposite to Pancasila. However, there are still many western culture influence economic system in Indonesia. In fact, almost all economists say that the liberal economic system and the global economic system that is initiated by the Western did not help to lift up the national economy and the welfare of Indonesian. Indonesia even further left behind from the western in terms of economic affairs. This is as a result of the economic system that is not based on human values and justice but principally on the strength of capital. Capitalist system built by the global economy resulted in displacement of the small people in the market competition, and it still benefited. Therefore, the legal system of Islamic economics could be an alternative in the midst of a national economic downturn.